Matty Doolin - Cookson, Catherine (Nxb. Đồng Nai, 2009)
Matty is fifteen and is leaving school in a few weeks' time. He wants to work with animals, and would like to get a job on a farm. But his parents say he's too young to leave home - he must stay in the town and get a job in ship-building, like his father. They also say he can't go on a camping holiday with his friends. And they say he can't keep his dog, Nelson, because Nelson barks all day and eats his father's shoes. But it is because of Nelson that Matty finds a new life ...